1996
DOI: 10.1097/00005537-199610000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Manometric Study of Complete Ostial Occlusion in Chronic Maxillary Atelectasis

Abstract: The effect of complete ostial occlusion on static pressure within the human maxillary sinus has not been previously studied. In this study, a novel way to directly determine maxillary sinus pressure is described. Maxillary sinus pressures were measured in five patients with chronic maxillary atelectasis (CMA); these values were compared to values obtained from the contralateral side and from patients with chronic sinusitis. Measurements were made by introducing an 18-gauge needle probe through the membranous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 15 publications
2
49
0
7
Order By: Relevance
“…This theory has been supported by studies in animal and human models. l3 , 14,38 Several authors have noted that after ostial occlusion of the maxillary sinus, specific mechanical changes occur. Upon the complete occlusion of the sinus, reabsorption occurs, along with the buildup of negative pressure from within the antrum.…”
Section: Summary Of All 84 Published Cases Of True Silent Sinus Syndromementioning
confidence: 99%
“…This theory has been supported by studies in animal and human models. l3 , 14,38 Several authors have noted that after ostial occlusion of the maxillary sinus, specific mechanical changes occur. Upon the complete occlusion of the sinus, reabsorption occurs, along with the buildup of negative pressure from within the antrum.…”
Section: Summary Of All 84 Published Cases Of True Silent Sinus Syndromementioning
confidence: 99%
“…SSS is a challenging diagnosis because it can be diagnosed in a subgroup of patients, who have the sinusal and orbital changes, but no specific symptoms of chronic rhinosinusitis. Kass et al 13 demonstrated in their study, comparing the pressure of the chronic maxillary atelectasis sinus with chronic maxillary sinusitis sinus and with a normal maxillary sinus, that the negative pressure is the basis of the chronic maxillary atelectasis. The negative pressure originates in the osteomeatal complex obstruction, determines bone remodeling and one of the most important signs, enophthalmos 2,6,7 .…”
Section: Discussionmentioning
confidence: 98%
“…Digital manometer connected to a rubber tube and a steel probe (top; right), as well as the data recording system. temperature and humidity, to reach the environmental requirements for the optimal function of the instrument 10,11 . Based on the observed parameters, the MSFE was calculated as the ratio between pressure values (∆p) observed in Group A or Group B p and the corresponding pressure values (∆p Standard ) of the control group…”
Section: Methodsmentioning
confidence: 99%